2-Arylaminobenzothiazole-arylpropenone conjugates as tubulin polymerization inhibitors. Issue 5 (7th March 2017) - Subba Rao, A. V.; Rao, Bala Bhaskara; Sunkari, Satish; Shaik, Siddiq Pasha; Shaik, Bajee; Kamal, Ahmed
Abstract : A new series of 2-arylaminobenzothiazole-arylpropenone conjugates were designed based on 5F-203, synthesized and evaluated for their cytotoxic potency as well as inhibition of tubulin polymerization. Abstract : A new series of 2-arylaminobenzothiazole-arylpropenone conjugates5 –6 (a –r ) was designed, synthesized and investigated for their cytotoxic potency against the various human cancer cell lines. Most of these conjugates exhibited cytotoxic activity and inhibited in vitro tubulin polymerization effectively. Conjugates5d and6d cause cell cycle blocks in the G2/M phase in HeLa cells and treatments with5d and6d manifested increased mRNA and protein levels of the G2/M marker, cyclin B1. Immunocytochemistry revealed loss of intact microtubule structure in cells treated with5d and6d . Western blot analysis revealed that these conjugates accumulate more tubulin in the soluble fraction. Moreover, the triggering of apoptotic cell death after mitotic arrest was investigated by studying their effect on Hoechst staining, mitochondrial membrane potential, ROS generation.